Theoretical models of comprehension skills tested through a comprehension assessment battery for primary school children. (April 2017) - Tobia, Valentina; Ciancaleoni, Matteo; Bonifacci, Paola
In this study, two alternative theoretical models were compared, in order to analyze which of them best explains primary school children's text comprehension skills. The first one was based on the distinction between two types of answers requested by the comprehension test: local or global. The second model involved texts' input modality: written or oral. For this purpose, a new instrument that assesses listening and reading comprehension skills (ALCE battery; Bonifacci et al., 2014) was administered to a large sample of 1, 658 Italian primary school students. The two models were tested separately for the five grades (first to fifth grade). Furthermore, a third model, that included both the types of answers and the texts' input modality, was considered. Results of confirmatory factor analyses suggested that all models are adequate, but the second one (reading vs. listening) provided a better fit. The major role of the distinction between input modalities is discussed in relation to individual differences and developmental trajectories in text comprehension. Theoretical and clinical implications are discussed.